Gloves, knives and heretical saints: the limits of self in the poetry of Luis Antonio de Villena - Rodríguez-Gaona, Martín (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
This essay explores the coherence of discourse and style in the poetry of Luis Antonio de Villena, something evident despite its diversity and scope. Through changes of tone and genre, the poet evokes the temporary and trascendental quality of human experience. This goal is achieved by constantly using some marks of style and discursive strategies: understanding culture as a substitute for human eternity, pain as the other side of beauty or pleasure and, finally, the creation and destruction of myths. Villena's approach defines that everything that is worth to translate into poetry has to be transformed by imagination, Following this strategy, his works show an unredeemable will to turn life into literature, and in this last stage the author of Asuntos de delirio takes a step further in what is known as social poetry, ending up in by proposing a pagan spiritualism, a new kind of belief or ideology, a symptom of metaphysical anxiety and rebellion.
Keywords: Luis Antonio de Villena; espiritualism